2019
DOI: 10.1161/circulationaha.118.039288
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Ability to Present Antigens on Major Histocompatibility Complex Class II Molecules Aggravates Atherosclerosis in ApoE −/− Mice

Abstract: Background: Hypercholesterolemic mice lacking factors required for activation of CD4 + T cells are characterized by reduced development of atherosclerosis. Consequently, it has been assumed that atherosclerosis involves loss of tolerance against modified self-antigens generated in response to hypercholesterolemia and that presentation of such antigens on major histocompatibility complex class II (MHCII) leads to activation of proatherogenic Th1 cells. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Our observation is in accordance with reports where anti-CD40 antibody treatment reduced atherosclerosis in LDLR −/− mice (72) and inhibition of Th1 responses reduced atherosclerosis in ApoE −/− mice (73). Recently, Wigren et al, and Williams et al, reported that global or B cell-specific deficiency of MHCII were associated with low level of total IgG and IgM as well as low or undetectable oxLDL specific antibodies (74,75), supporting our data by defining differential roles of a B cell-specific MHCII and CD40 in generation of plasma cells and antibodies. Interestingly, in contrast to increased atherosclerosis in MHCII −/− ApoE −/− double knockout mice (74), MHCII deficiency on B cells did not affect atherosclerosis in LDLR −/− mice despite large but incomplete reductions in MHCII in B cells (75); reductions resulted in reduced IgG1 and IgG2c but not IgG2b nor IgM.…”
Section: Discussionsupporting
confidence: 87%
“…Our observation is in accordance with reports where anti-CD40 antibody treatment reduced atherosclerosis in LDLR −/− mice (72) and inhibition of Th1 responses reduced atherosclerosis in ApoE −/− mice (73). Recently, Wigren et al, and Williams et al, reported that global or B cell-specific deficiency of MHCII were associated with low level of total IgG and IgM as well as low or undetectable oxLDL specific antibodies (74,75), supporting our data by defining differential roles of a B cell-specific MHCII and CD40 in generation of plasma cells and antibodies. Interestingly, in contrast to increased atherosclerosis in MHCII −/− ApoE −/− double knockout mice (74), MHCII deficiency on B cells did not affect atherosclerosis in LDLR −/− mice despite large but incomplete reductions in MHCII in B cells (75); reductions resulted in reduced IgG1 and IgG2c but not IgG2b nor IgM.…”
Section: Discussionsupporting
confidence: 87%
“…Global MHC-II deficiency aggravates atherosclerotic lesions in Ldlr −/− mice due to a decrease in Tregs, despite a decrease in systemic inflammation [160]. In this model, the role of B cells is difficult to estimate, as MHC-II-mediated antigen presentation is also performed by DCs and to a lesser extent, by MΦs.…”
Section: Antigen Presentation and Co-stimulatory Moleculesmentioning
confidence: 99%
“…The importance of antigen presentation by APCs in atherosclerosis has been revealed by several studies. In LDLR −/− mice, abrogation of the invariant chain of CD74, a protein involved in MHCII-peptide complex formation [288], reduces T cell activation and atherosclerosis; however, in ApoE −/− mice, the inability to present antigens on MHCII increases atherosclerosis by reducing the pool of atheroprotective Tregs and increasing proatherogenic CD8 + T cells [289]. The reason for this discrepancy is unknown, but an atheroprotective role of antigen presentation via MHCII is supported by the finding that TLR-activated CD11c + DCs promote Treg development and function in association with increased atherosclerosis [290].…”
Section: Innate Immunitymentioning
confidence: 99%
“…Recent studies suggest that indirect modulation of the Th2 response is atheroprotective. MHCII −/− ApoE −/− double knockout mice show aggravated atherosclerosis and reduced levels of Th2 cytokines in plasma [289]. Similarly, CCL1 −/− ApoE −/− mice show increased atherosclerosis and an elevated splenocytic Th1:Th2 ratio [404], whereas IL-12p35 −/− ApoE −/− mice show reduced atherosclerosis and a reduced Th1:Th2 ratio [405].…”
Section: Adaptive Immunitymentioning
confidence: 99%